Senam Tera Berpengaruh terhadap Tekanan Darah pada Lansia dengan Hipertensi - Setiawati, Si Ayu Rai; Lestari, Agus Sri; Gama, Ketut; Suardana, Ketut; Harini, I Gusti Ayu (Jurnal Gema Keperawatan, 2023)
The decline in physical condition in the elderly causes limited movement so that the elasticity of blood vessels becomes reduced. This condition becomes a predisposing factor of hypertension. This study aims to determine the effect of tera gymnastics on blood pressure in the elderly with hypertension in the working area of Puskesmas II West Denpasar in 2023. This type of research is quasi-experimental designs using a one-group pretest-posttest design. The number of samples was 36people using a non-probability sampling technique, namely purposive sampling. This study was conducted for 2 weeks with 6 interventions. Blood pressure measurement was done before the intervention was given then did a tera gymnasticsintervention for 30 minutes and blood pressure measurement was done again after 6 interventions. Data was analyzed by paired t-test. The results of the study found that the average systolic blood pressure before the intervention was 155.89 mmHg and diastolic was 98.14 mmHg. The mean systolic blood pressure after the intervention was 134.42 mmHg and diastolic was 90.67 mmHg. . The results of the statistical test obtained a p-value of 0.001 (p-value 0.05) so that it can be concluded that there is an effect of tera gymnastics on blood pressure in the elderly with hypertension in the work area of Puskesmas II West Denpasar in 2023. It is recommended that tera gymnastics be carried out regularly at least 3 times a week and used as a non-pharmacological therapy to lower blood pressure in hypertensive elderly in the work area of Puskesmas II West Denpasar.